Aging into Medicare among a senior food pantry population: An assessment of food pantry visit patterns and food security over time. Issue 2 (17th March 2022) - Martinez‐Miller, Erline E.; Leonard, Tammy; Pruitt, Sandi L.
Abstract: We examined the association of Medicare eligibility with seeking charitable food assistance and food security status among low‐income senior clients (≥60 years) of a food pantry in Dallas, Texas. We used sharp regression discontinuity to examine the impact of aging into Medicare on food pantry visit patterns among nondisabled senior households, and log‐binomial regression to assess the association between Medicare‐eligible visits and food security status. Medicare eligibility was associated with more food pantry visits and improved food security. Medicare eligibility may improve food security among seniors, potentially attributable to increased food pantry use after aging into Medicare.